Biodiversity Implications of Riparian Home-gardens: the Case of Chalakkudy River Based Agro-Ecosystem in Kerala - Thomas, Allan; Thomas, Usha C.; Kishore Kumar, N (Journal of Extension Education, 2017)
Riparian home-garden farming systems are human landscapes that are sustainable,fulfilling the different pillars of socio-economic and environmental stability. This explorative study conducted in the 60 selected home-gardens in the left-right riparian banks of Chalakkudy river in Kerala, India casting the upper reaches and middle to lower reaches aimed to assess the crop diversity of tropical riparian home-gardens in terms of diversity index. Altogether 60 home-gardens were analysed and the Shannon – Wiener index of Biodiversity was found to be 1.518 in the upper riparian reaches and for the middle to lower reaches the average diversity index was 1.453 indicating erosion in biodiversity in home-gardens cascading towards middle to lower reaches of the riparian corridors.